The turn-taking mechanism in the City Council deliberation on Ordinance No. 029, series of 2002 (Otherwise known as an Ordinance Amending the Ordinance No. 3816, series of 1996) - Montibon, Rezsa L.
This study was conducted to determine the turn-taking mechanism used in the deliberation of the City Council of the Sanguniang Panglungsod of Davao City on the relevance of the anti-smoking ordinance. The research further aimed to describe the social arrangement of the City Council, and to make turn-taking participation framework. The turn-taking theory of Sacks, Schegloff and Jefferson were used in the analysis of the turn-taking process used in the City Council. The study also applied the concepts of reciprocity and adjacency pair as a social control mechanism based on the level of participants, the researcher constructed a turn-taking participation framework. The participation framework described the roles assumed by the participants in the discussion and identified the active and non-active participants. The conversation analysis was used in the scrutinizing the nature of the deliberation in the Council on the resolution to enact Ordinance No. 029, series of 2002, otherwise known as ?An Ordinance amending sections 1, 2, 3, 4, and 5 of Ordinance No. 3816, series of 1996? (Ord. No. 029-02). The study concentrated on the presentation of the ordinance to the Council by the Committee on Rules, Laws and Privileges on April 3, 2002. The primary data of this study was the transcription of the proceeding of the 14th regular session of the 13th Council of the Sanguniang Panglungsod of Davao City. The researcher examined the utterances of the city councilors. The speech acts employed by these utterances were identified. The acts performed by the participants that completed each other were then tied up together to make adjacency pairs. The adjacency pairs reflected the turn-taking mechanism and the social control mechanism in the deliberation. The members of the City Council deliberated to discuss the pros and cons of the ordinance. It is a part of their study as public officials. The participants employed some strategies that enabled them to take the floor. The three strategies of turn-taking mechanism were: turn yielding, turn holding and turn taking. Discourse makers were found to be frequently used by the participants to state their desire to yield, hold and take the floor. The result of the study showed that the City Council was organized and that they were able to follow the rule of reciprocity though were was low participation in the discussion. The social achievement of the Council at the end of their discussion was the amendment on the revision of the Sanguniang Panglungsod of Davao City. Few studies are available in the Philippine context regarding the analysis of the deliberation process. Thus, the results of this study serve as an additional reference for future studies on conversation analysis using the turn-taking theory in political institution.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication